A dual bevel compact planar monopole antenna for UHF application - Jusoh, M. (2012)
This paper presented a novel dual bevel planar monopole antenna with the ability to operate from 470MHz to 1100 MHz. The compact planar monopole antenna consists of radiating element perpendicular to ground plane with dimension of 148mm 64mm and 80mm square respectively. The proposed monopole antenna employing FR4 substrate and implementing beveling technique as well re°ect to the low cost and high bandwidth intention. By introducing a dual bevel, an enhancement of 100% impedance bandwidth can be achieved compare to a single bevel with the same bevel angle of 10±, 20±, 30±, 40± and 50±. Moreover, the dual bevel antenna capable in producing divisive radiation patterns with linear polarization at three different fre-quencies of f1 = 500 MHz, f2 = 700MHz and f3 = 900 MHz. The measured outputs have shown the same behaviour with the simulation results. The proposed antenna has a great potential as a spectrum sensing device for cognitive radio application in the future.